Hygrosopicity measurements of aerosol particles in the San Joaquin Valley, CA, Baltimore, MD, and Golden, CO - Orozco, Daniel; Beyersdorf, A. J.; Ziemba, L. D.; Berkoff, T.; Zhang, Q.; Delgado, R.; Hennigan, C. J.; Thornhill, K. L.; Young, D. E.; Parworth, C.; Kim, H.; Hoff, R. M. (John Wiley & Sons, Inc., 2016)
Aerosol hygroscopicity was investigated using a novel dryer-humidifier system, coupled to a TSI-3563 nephelometer, to obtain the light scattering coefficient (sscat) as a function of relative humidity (RH) in hydration and dehydration modes. The measurements were performed in Porterville, CA (10 January to 6 February 2013), Baltimore, MD (3-30 July 2013), and Golden, CO (12 July to 10 August 2014). Observations in Porterville and Golden were part of the NASA-sponsored Deriving Information on Surface Conditions from Column and Vertically Resolved Observations Relevant to Air Quality project. The measured sscat under varying RH in the three sites was combined with ground aerosol extinction, PM2.5 mass concentrations, and particle composition measurements and compared with airborne observations performed during campaigns. The enhancement factor, f(RH), defined as the ratio of sscat( RH) at a certain RH divided by sscat at a dry value, was used to evaluate the aerosol hygroscopicity. Particles in Porterville showed low average f(RH=80%) (1.42) which was attributed to the high carbonaceous loading in the region where residential biomass burning and traffic emissions contribute heavily to air pollution. In Baltimore, the high average f(RH=80%) (2.06) was attributed to the large contribution of SO42- in the region. The lowest water uptake was observed in Golden, with an average f(RH=80%)=1.24 where organic carbon dominated the particle loading. Different empirical fits were evaluated using the f( RH) data. The widely used Kasten ( gamma) model was found least satisfactory, as it overestimates f( RH) for RH < 75%. A better empirical fit with two power law curve fitting parameters c and k was found to replicate f( RH) accurately from the three sites. The relationship between the organic carbon mass and the species that are affected by RH and f( RH) was also studied and categorized.